Briefing on existing food system monitoring frameworks and indicators developed by RUAF with FAO and various cities (2016-2022) - Carey, Joy (CGIAR System Organization, 2022)
Within the CGIAR Resilient Cities Initiative, RUAF is applying an approach to food system monitoring frameworks and indicators that has been developed, tried and tested in a number of cities globally since 2016. This briefing document shares and explains previous work done by RUAF to develop tools for assessing and tracking food system transformation at both a city and city region level. The experience of conducing indicators work under Resilient Cities contributes to on-going development of the approach and will help inform future applications.